Estimations of plasma potential and density by the heavy ion beam probing diagnostics on the Uragan-2M torsatron - Komarov, A.D.; Chmyga, A.A.; Chechkin, V.V.; Grigor’eva, L.I.; Deshko, G.N.; Kozachek, A.S.; Krupnik, L.I.; Khrebtov, S.M.; Maznichenko, S.M.; Mironov, Yu.K.; Romanov, V.S.; Zhezhera, A.I. (Вопросы атомной науки и техники, 2016)
First estimations of plasma electric potential and density in URAGAN -2M (U-2M) torsatron were done by the Heavy Ion Beam Probing Diagnostic (HIBP). The estimated plasma potential has the negative potential value of -(80…195) V. The experimental values of the secondary ion beam current are well correlated with average plasma density measured by radio-interferometer - (1.25… 2.5)×10¹² cm⁻³ . Notable oscillations of the secondary beam current were observed, which were caused by fluctuations of the torsatron magnetic field. С помощью диагностического комплекса зондирования плазмы пучком тяжёлых ионов (ЗППТИ) на торсатроне УРАГАН-2М проведена предварительная оценка потенциала и плотности плазмы. Оценка дала значение отрицательного потенциала на уровне -(80…195) В. Полученные экспериментальные значения плотности плазмы достаточно хорошо соответствуют измерениям средней плотности плазмы с помощью интерферометра - (1.25…2.5)x10¹² см⁻³. Зарегистрированы колебания тока вторичных ионов, обусловленные флуктуациями магнитного поля торсатрона. За допомогою діагностичного комплексу зондування плазми пучком важких іонів (ЗППВІ) на торсатроні УРАГАН-2М були проведені попередні оцінки потенціалу та густини плазми. Оцінка дала значення негативного потенціалу на рівні -(80…195) В. Одержані експериментальні значення густини плазми збігаються з вимірюванням середньої густини плазми за допомогою інтерферометра - (1.25…2.5)x10⁻¹² см⁻³.. Зареєстровані коливання струму вторинних іонів, які обумовлені флуктуаціями магнітного поля торсатрону.